Philosophy of the performing arts - Davies, David (Oxford : Wiley-Blackwell, 2011)
Part One Performance and the Classical Paradigm. 1 The Nature of Artistic Performance. 1 Introduction. 2 What is a Performance? 3 Institutional Theories of Artistic Performance. 4 Aesthetic Theories of Artistic Performance. 5 Artistic Performance and Artistic Regard. 6 Overview. 2 The Classical Paradigm I: The Nature of the Performable Work. 1 Introduction: Berthold and Magda Go to the Symphony. 2 The Multiple Nature of Performable Works. 3 Performable Works as Types. 4 Varieties of Type Theories: Sonicism, Instrumentalism, and Contextualism. 5 Other Theories of the Performable Work. 3 The Classical Paradigm II: Appreciating Performable Works in Performance. 1 Introduction: Talking Appreciatively about Performable Works. 2 Can Performable Works Share Artistic Properties with Their Performances? 3 The Goodman Argument. 4 Answering the Goodman Argument. 4 Authenticity in Musical Performance. 1 Introduction. 2 Authenticity in the Arts. 3 Three Notions of Historically Authentic Performance. 5 Challenges to the Classical Paradigm in Music. 1 Introduction: The Classical Paradigm in the Performing Arts. 2 The Scope of the Paradigm in Classical Music. 3 Jazz, Rock, and the Classical Paradigm. 4 Non-Western Music and the Classical Paradigm. 6 The Scope of the Classical Paradigm: Theater, Dance, and Literature. 1 Introduction: Berthold and Magda Go to the Theater. 2 Theatrical Performances and Performable Works. 3 Challenges to the Classical Paradigm in Theater. 4 Dance and the Classical Paradigm. 5 The Novel as Performable Work? Part Two Performance as Art. 7 Performances as Artworks. 1 Introduction: Spontaneous Performance in the Arts. 2 The Artistic Status of Performances Outside the Classical Paradigm. 3 The Artistic Status of Performances Within the Classical Paradigm. 8 Elements of Performance I: Improvisation and Rehearsal. 1 Introduction. 2 The Nature of Improvisation. 3 Improvisation and Performable Works: Three Models. 4 Improvisation and Recording. 5 The Pl
Includes bibliographical references and index.
boek